Loving, taking care, subjectivizing _ educational implications in early childhood - Baptista, Valéria Ferranti (Clinical Styles. The Journal on the vicissitudes of childhood, 2003)
When the child acquired mercantile value, its survival became an imperative and the high mortality rate which characterized the Ancien Régime became an evil that had to be met with. Through the guidance of illustrated men, baby education was promoted, and the mother was invoiced to protagonize this new chapter in the childhood history. Her mission was to take care of her offspring not by moral obligations, but by love. Since then a conjunction of care, loving and education began. Based on Lacan's ideas it is possible to separate these terms and review their implication in the educational practices of early childhood